Early Modern Netherlandish Artists on Proportion in Architecture, or 'de questien der Simmetrien met redene der Geometrien'. Issue 1 (20th June 2014) - De Jonge, Krista
Abstract : The question of geometrical and/or/ versus arithmetical proportions remains unresolved insofar as Netherlandish Early Modern architectural production is concerned. A newly discovered manuscript book on the orders that can be attributed to a Netherlandish artist active in the 1530s confirms the need for a less antithetical interpretation of Renaissance proportional systems in northern European architecture than has been common in the scholarship to date. Beginning in the 1530s, a geometrical way of expressing both geometrical and arithmetical proportions was developed, connecting both masters of the "antique" and of the "modern" through one notation system understandable by all. This article traces its offshoots until the seventeenth century.